Ð—Ð°Ð²Ð¸ÑÐ¸Ð¼Ð¾ÑÑ‚ÑŒ Ð½Ð°Ð¿Ñ€ÑÐ¶ÐµÐ½Ð¸Ñ ÑÐ´Ð²Ð¸Ð³Ð° Ð¾Ñ‚ Ð³ÐµÐ¼Ð°Ñ‚Ð¾ÐºÑ€Ð¸Ñ‚Ð° Ð¿Ñ€Ð¸ Ð¿Ñ€Ð¾Ñ‚ÐµÐºÐ°Ð½Ð¸Ð¸ ÑÑƒÑÐ¿ÐµÐ½Ð·Ð¸Ð¸ ÑÑ€Ð¸Ñ‚Ñ€Ð¾Ñ†Ð¸Ñ‚Ð¾Ð² Ñ‡ÐµÑ€ÐµÐ· ÑƒÐ·ÐºÐ¸Ðµ Ð¿Ð»Ð¾ÑÐºÐ¸Ðµ ÐºÐ°Ð½Ð°Ð»Ñ‹ - Todrin, A. F.; Usachov, V. V.; Timofeyeva, E. V. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2006)
The paper covers the research results on shift tension during flowing of erythrocyte suspension through narrow flat channels. The dependency of shift tension on the hematocrit was obtained and there was shown the possibility to reduce the tension value at measured hematocrit value to the shift tension with the set hematocrit of suspension.